Arga Math: Sosialisasi Plakat untuk Meningkatkan Kemampuan Belajar Eksponen Siswa - Fhadillah, Alda Sri Ayu; Asfar, Andi Muhammad Irfan Taufan; Aspikal, Aspikal (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The PLAKAT (Rank Number Board) socialization activity aims to introduce innovative teaching aid to educational partners. This tool is designed to enhance student interest and motivation while simplifying the understanding of the abstract concept of exponents. In addition, it encourages educators to develop creative instructional media, thereby contributing to a more engaging and effective mathematics learning environment. Research Methodology: The activity was conducted at MTS Sinoa using a knowledge transfer model through a service-learning approach. Partners received a brief presentation on the PLAKAT teaching aid, followed by hands-on practice using the tool. To evaluate perceptions, participants completed a questionnaire assessing their understanding of and views on the usefulness of the teaching aid. Results: Socialization significantly improved both teacher and student understanding and ability to use the PLAKAT tool. Exponent materials became more accessible and engaging for students, while teachers were inspired to innovate in designing and implementing relevant learning media. Overall, the activity enhanced motivation and creativity in the teaching and learning process, aligning with curriculum goals. Conclusions: The PLAKAT teaching aid effectively increased the awareness and application of visual learning tools in mathematics. Its use promotes deeper comprehension and stimulates both educator and student creativity. Limitations: Challenges included limited participation—only 13 eighth-grade students and few educators attended, as the activity took place during class hours. Contribution: This initiative supports SDG Goal 4 on quality education by offering practical solutions to improve educational methods and address global learning challenges.